In-situ mulching of weeds in pigeon pea - Singh, R. K.; Jaiswal, R. K. (Indian Farming, 2015)
In pigeon pea cultivation, weeds are considered as major important factor for reducing pigeon pea production. About 40% reduction in pigeon pea yield occurred due to heavy infestation of weeds. In present scenario, the chemical herbicides arebeing used to control different weeds flora however, it has certainlimitations such as emergence of resistance in the weeds, hazardous effect over beneficial microbes, crops and environment, etc which prevent them to be used widely for thecontrol of weeds. In this regard, manual weeding along with in-situ mulching may be a very common, ecofriendly and approachable practice for the management of weeds inpigeon pea cultivation. The practice of in-situ mulching along withbalanced dose of fertilizers and selection of extra short-durationcultivar (ICPL-88039) respectively maximized the yield of pigeon pea by 35.76 and 109 per cent over uses of pre-emergence weedicide, hand weeding and control. Maximum cost benefit ratio was obtained from insitu mulching of weeds (1:2.6) followed by hand weeding (1:2.3) pre-emergence weedicide (1:2.0) andcontrol (1:1.6). Selection of extra short-duration variety, use of balanced dose of fertilizer along with in-situ mulching of weeds is quite successful and ecofriendly practice for raising pigeon pea production under rainfed condition.